Exercise Training Lowers the Enhanced Tonically Active Glutamatergic Input to the Rostral Ventrolateral Medulla in Hypertensive Rats - Zha, Yan‐Ping (CNS Neurosci Ther, 2013)
AIMS: It is well known that low‐intensity exercise training (ExT) is beneficial to cardiovascular dysfunction in hypertension. The tonically active glutamatergic input to the rostral ventrolateral medulla (RVLM), a key region for control of blood pressure and sympathetic tone, has been demonstrated to be increased in hypertensive rats. The aim of this study was to determine the effect of ExT on the increased glutamatergic input to the RVLM in spontaneously hypertensive rat (SHR). METHODS: Normotensive rats Wistar‐Kyoto (WKY) and SHR were treadmill trained or remained sedentary (Sed) for 12 weeks and classed into four groups (WKY‐Sed, WKY‐ExT, SHR‐Sed, and SHR‐ExT). The release of glutamate in the RVLM and its contribution to cardiovascular activity were determined in WKY and SHR after treatment of ExT. RESULTS: Blood pressure and sympathetic tone were significantly reduced in SHR after treatment with ExT. Bilateral microinjection of the glutamate receptor antagonist kynurenic acid (2.7 nmol in 100 nL) into the RVLM significantly decreased resting blood pressure, heart rate, and renal sympathetic nerve activity in SHR‐Sed but not in WKY groups (WKY‐Sed and WKY‐ExT). However, the degree of reduction in these cardiovascular parameters evoked by KYN was significantly blunted in SHR‐ExT compared with SHR‐Sed group. The concentration of glutamate and the protein expression of vesicular glutamate transporter 2 in the RVLM were significantly increased in SHR‐Sed compared with WKY‐Sed, whereas they were reduced after treatment with ExT. CONCLUSION: Our findings suggest that ExT attenuates the enhancement in the tonically acting glutamatergic input to the RVLM of hypertensive rats, thereby reducing the sympathetic hyperactivity and blood pressure.